A Pilot Study into the Effects of the CB1 Cannabinoid Receptor Agonist WIN55, 212-2 or the Antagonist/Inverse Agonist AM251 on Sleep in Rats. (4th January 2012) - Goonawardena, Anushka V.; Plano, Andrea; Robinson, Lianne; Platt, Bettina; Hampson, Robert E.; Riedel, Gernot
Abstract : The plant cannabinoid Δ 9 -tetrahydrocannabinol and the endocannabinoid anandamide increase the amount of sleep via a CB1 receptor mediated mechanism. Here, we explored the use of a novel electroencephalogram (EEG) recording device based on wireless EEG microchip technology (Neurologger) in freely-moving rats, and its utility in experiments of cannabinoids-induced alterations of EEG/vigilance stages. EEG was recorded through epidural electrodes placed above pre-frontal and parietal cortex (overlaying the dorsal hippocampus). As cannabinoids, we acutely administered the full synthetic CB1 receptor agonist, WIN55, 212-2 (1 mg/kg), and the antagonist/inverse agonist, AM251 (2 mg/kg), either alone or together through the intraperitoneal route. WIN55, 212-2 increased the total amount of NREM sleep and the length of each NREM bout, but this was unlikely due to CB1 receptor activation since it was not prevented by AM251. However, WIN55, 212-2 also lowered overall EEG spectral power especially in theta and alpha frequency bands during wakefulness and NREM sleep, and this effect was reversed by AM251. The antagonist/inverse agonist caused no sleep alterations by itself and moderately increased spectral power in Theta, alpha and beta frequency bands during NREM sleep when administered on its own. Implications of endocannabinoid modulation of the sleep-wake cycle and its possible interactions with other transmitter systems are considered.